Strategi Pengembangan Lembaga Pendidikan Nonformal Yayasan Tarbiyah Syamilah Di Kabupaten Ogan Ilir - Putri, Nurul Tarisa; Suryati, Suryati; Noviza, Neni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This thesis is entitled "Strategy for the Development of Non-formal Education Institutions of the Tarbiyah Syamilah Foundation in Ogan Ilir Regency. The purpose of this study was to determine the strategy for the development of non-formal educational institutions of the Tarbiyah Syamilah Foundation in Ogan Ilir District, the constraints and influences of the development of the Tarbiyah Syamilah Foundation's non-formal educational institutions in Ogan Ilir District. This type of research is field research, namely research that seeks data in the field to support the theory used. The method or approach used is descriptive qualitative using data collection techniques through observation, interviews, and documentation. In conducting the interviews, there were 4 (four) informants, namely the chairman of the Tarbiyah Syamilah Foundation's daily administrator as a key informant, the daily administrator of the Atrbiyah Syamilah Foundation as the main informant, and the chairman and members of the RMT Tarbiyah Syamilah unit as supporting informants. Then, the validity of the data was checked using technical triangulation and source triangulation. The results of the study show that the strategy for developing non-formal educational institutions at the Tarbiyah Syamilah Foundation in Ogan Ilir Regency uses the master strategy theory which consists of enterprise strategy, corporate strategy, business strategy, and functional strategy. The obstacles faced in the development of the Syamilah Tarbiyah Foundation were the limited infrastructure and development funds due to the absence of permanent donors. In addition, Tarbiyah Syamilah sometimes still lacks human resources. Departing from the theory of Kiai Sahal Mahfud in the book on Islamic community development that the development and development of society through the actualization of amar ma'ruf nahi munkar behavior as in Qs. Ali Imran verse 110 and being part of da'wah bil-hal, namely preaching with real actions, the influence of the development of non-formal educational institutions of the Tarbiyah Syamilah Foundation is marked by the implementation of literacy education programs, vocational education, general education and counseling, as well as soul-freshening education.